Analysis of the effect of different doses of rooting in soybean cultivation (Glicine max L. Merril) via regression model - Humada Gonzalez, Guido; Franco Nuñez, Karina; cavalheiro, Flavio (Pubvet, 2021)
To analyze the effect of different doses of rooting in soybean (Glycine max L. Merril) cultivation, an experiment was carried out in Caaguazu Departament with coordinates 25º 24’ 7.5’’S y 54º 51’ 29.3’’W. The experiment was carried out between September 2018 and January 2019. Twenty experimental units were evaluated arranged in complete random blocks. The treatments consisted of four different kinds of rooting (0,2,4,6) expressed in ml with 5 repetitions for each of the treatments. To establish the optimal dose of rooting, a regression analysis was performed using the segmented linear model with plate response. Under the conditions in which the experiments were carried out, the results show that the optimal dose of rooting which maximizes productivity is equal to 5,08 ml/kg of Fertiactyl LEG, which obtains a productivity of 3,809 kg/ha. The determination coefficient also proves that the segmented linear model with plate reply, is suitable to show events that are related to the yield vs doses.